Do athletes modify the neuromuscular control of landing after participation in landing training programs? - Munro, B.; Stelle, J. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
basketball and have been found to be beneficial to players in terms of reducing knee injuries. However, the mechanisms by which these injuries are reduced remain speculative. Therefore, the purpose of this study was to determine the effects of participation in a landing training program on the neuromuscular control patterns displayed by athletes during abrupt deceleration landing tasks. Twenty athletes (mean 22.9 years, range 19-30) involved in landing sports and with no history of knee joint disease were randomly assigned to either a landing trained or control group. The landing trained group participated in a six week landing training program focusing on correct landing mechanics, completing three 30 minute training sessions per week. All subjects underwent laboratory-based assessment of their landing technique preand post-intervention. During landing assessment, each subject`s three-dimensional deceleration motion was captured (200 Hz) using an OPTOTRAK 3020 motion analysis system, their kinetics of landing were collected (1000 Hz) using a Kistler Multichannel force platform and their lower limb neuromuscular control patterns were collected (1000 Hz) using the Noraxon Telemyo system. Independent t-tests conducted on the percentage change data were conducted to determine the significant (p 0.05) effects of participating in the landing training program on the kinematic, kinetic and neuromuscular control strategies used when the subjects performed the abrupt deceleration landing tasks. It is postulated that the changes that occurred as a result of the landing training may allow practitioners/trainers to identify why landing training is beneficial to athletes to prevent knee injuries in the field.